KONSELING PEMBERIAN TUMIS JANTUNG PISANG KEPOK UNTUK MENINGKATKAN PRODUKSI ASI TERHADAP PENGETAHUAN PADA IBU NIFAS DI PUSKESMAS JELBUK - ummi masruroh; yuni handayani; dinar perbawati (LPPM Universitas dr. Soebandi, 2026)
Background: Inadequate breast milk production among postpartum mothers remains a common health issue in both urban and rural areas. One of the main contributing factors is the lack of understanding about proper nutritional intake needed to support the lactation process. The heart of the kepok banana is a local food ingredient that is easy to find and contains lactagogic compounds such as flavonoids and polyphenols. These compounds play an important role in stimulating the hormones prolactin and oxytocin, which are essential for enhancing milk production and secretion. objective: This activity aimed to improve postpartum mothers’ knowledge about the benefits of kepok banana heart in promoting smoother breast milk production as part of supporting exclusive breastfeeding. Methods/Activity Stages: This community service activity was carried out at Puskesmas Jelbuk, targeting 16 postpartum mothers who experienced insufficient milk production. The method included pretest and posttest evaluations to assess knowledge before and after the counseling sessions, as well as interactive lectures and discussions.Results: The results showed a significant increase in knowledge, with the average pretest score of 60 rising to 80 in the posttest following the counseling intervention. Conclusion: Counseling on the benefits of kepok banana heart proved effective in enhancing postpartum mothers’ understanding of natural alternatives to improve breast milk production. Such educational initiatives are crucial in supporting the sustained health of both mothers and infants. Suggestion: Education on the benefits of kepok banana heart should be provided regularly to help postpartum mothers better improve their breast milk production.